2009
DOI: 10.1111/j.1751-3928.2009.00100.x
|View full text |Cite
|
Sign up to set email alerts
|

Geochemistry of K‐feldspar and Muscovite in Rare‐element Pegmatites and Granites from the Totoral Pegmatite Field, San Luis, Argentina

Abstract: The geochemistry of K-feldspar for K, P, Sr, Ba, Rb, Cs, Ga, and of muscovite for the same elements plus Nb and Ta, was used for proving the parental relationships of S-type granites and LCT (Li, Cs, Ta) rare-element pegmatites in the southernmost pegmatitic field of the Pampean pegmatite province in Argentina. The variation of K/Rb-Cs, K/Cs-Rb, K/Rb-Rb/Sr, K/Rb-Ba in K-feldspar from the granites and pegmatites show that they form an association with the evolutional sequence: granites → barren-to transitional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0
5

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(15 citation statements)
references
References 20 publications
2
8
0
5
Order By: Relevance
“…Furthermore, it was observed that Ba in pegmatitic muscovite shows a positive correlation with the K/Rb-ratio (figures 6a). Crystallization of feldspars and micas has been reported to result in progressive depletion of Ba and Sr (Jolliff et al, 1992;Oyarzábal et al, 2009;Roda-Robles et al, 2012;Vieira et al, 2011).The Ba-data are thus likewise in accordance with an evolution that can be attributed to fractional crystallization. This is not the case for Sr, as a positive…”
Section: Fractional Crystallization In the Pegmatitessupporting
confidence: 62%
See 1 more Smart Citation
“…Furthermore, it was observed that Ba in pegmatitic muscovite shows a positive correlation with the K/Rb-ratio (figures 6a). Crystallization of feldspars and micas has been reported to result in progressive depletion of Ba and Sr (Jolliff et al, 1992;Oyarzábal et al, 2009;Roda-Robles et al, 2012;Vieira et al, 2011).The Ba-data are thus likewise in accordance with an evolution that can be attributed to fractional crystallization. This is not the case for Sr, as a positive…”
Section: Fractional Crystallization In the Pegmatitessupporting
confidence: 62%
“…K/Rb versus Cs in muscovite has been reported to be a reliable indicator of pegmatite evolution (e.g. Černý et al, 1985;Jolliff et al, 1992;Oyarzábal et al, 2009;Roda-Robles et al, 2012;Vieira et al, 2011). During fractional crystallization, bulk incompatible elements get enriched in the residual melt, while bulk compatible elements get depleted.…”
Section: Fractional Crystallization In the Pegmatitesmentioning
confidence: 99%
“…The surrounding gneisses pertain to the cordierite-sillimanite facies indicative of temperatures slightly higher (650°C) than the temperature determined for the pegmatite itself (500 to 600°C) (Holdaway and Lee, 1977). Examples from the pegmatite in northern Norway, from Malawi and the San Luis pegmatite province, NW Argentina, corroborate this idea of types III and IV zircon to be used as an ore guide to and within a pegmatite province (Dill, 2007;Oyarzábal et al, 2009;Pedersen et al, 1989;Roberts et al, 2006) (Fig. 9).…”
Section: Morphology Of Zircon and Its Originsupporting
confidence: 53%
“…The plot of K/Rb vs. Cs for K-feldspars from Cerro La Torre granites and the intermediate zones of the pegmatites shows a linear fractionation trend (Fig. 2, Oyarzábal et al 2009). This, together with the known ages for the granites and pegmatites of the Totoral pegmatite field (centred at ~455 Ma, von Quadt and Galliski 2011), supports the interpretation that all of them are cogenetic (Galliski 2013 …”
Section: Introductionmentioning
confidence: 99%
“…Beryl-columbite-phosphate subtype pegmatites containing beusite-lithiophilite phosphate assemblages occur near the granite and pass eastwards to albite-type pegmatites very near to the transition from mica schist to phyllite (Oyarzábal et al 2009). The beryl-type pegmatites are disharmonically folded showing evidence of strong deformation.…”
Section: Introductionmentioning
confidence: 99%